Knowledge Experiments: Technology and the Library - Mickiewicz, Paulina (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2011)
The 21st century library has become a central nervous system for new and emergent media technologies, a site that centralizes increasingly decentralized networks and systems, and a localizable place in which new and emergent media technologies have not only found a home, an embodied place where they can be contained, but also a broader site in which the encounter between citizens, public knowledge and culture is staged. This article seeks to explore the “technologization” of the library. More specifically, it examines how this process of “technologization” has transformed the ways we use and understand the library as a public space and what this means for its future. The idea of the library as an important medium in itself has been overlooked in the broader context of communication and media studies.